PENGARUH TRANSPARANSI, PARTISIPASI DAN AKUNTABILITAS TERHADAP KINERJA PERANGKAT DESA SE-KECAMATAN LOHIA KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - Neti Neti; Nurwati Nurwati; Salma Saleh (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
This study aims to examine and analyze the effect of transparency, participation and accountability on the performance of village officials in Lohia District, Muna Regency, Southeast Sulawesi Province. This research is a quantitative approach. The population in this study was village officials in Lohia District, Muna Regency, Southeast Sulawesi Province with a sample of 63 people. The analysis used multiple regression analysis with the help of IBM SPSS 22 Software.The results of the study show that (1) Transparency, participation and accountability together have a positive and significant effect on the performance of village officials in Lohia District, Muna Regency, Southeast Sulawesi Province (2) Transparency has a positive and significant effect on the performance of village officials in Lohia District, District Muna, Southeast Sulawesi Province, (3) Participation has a positive and significant effect on the performance of village officials in Lohia District, Muna Regency, Southeast Sulawesi Province, and (4) Accountability has a positive and significant effect on the performance of village officials.